METHODS OF TEXT LINGUISTIC EXPERTISE - Zakhro Shadmankulovna Abdullaeva (PEDAGOGS, 2024)
Annotation: This article provides information on the systematization of special methodological principles and categories in linguistic examination of the text. The general laws of the linguistic examination of the text, as well as the linguistic principles of determining the meaning in the speech, are based on the dialectics of thought and speech, form and content, speech and logic.